Barriers and facilitators for breast cancer early diagnosis in an indigenous community in Mexico: voices of otomí women - Minerva Saldaña-Téllez; Sergio Meneses-Navarro; Leonor Cano-Garduño; Karla Unger-Saldaña (BMC, 2024)
Abstract Background Literature on barriers and facilitators for early detection of Breast Cancer (BC) among indigenous women is very scarce. This study aimed to identify barriers and facilitators for BC early diagnosis as perceived by women of the otomí ethnic group in Mexico. Methods We performed an exploratory qualitative study. Data was collected in 2021 through three focus group interviews with 19 otomí women. The interview transcripts were analyzed using the constant comparison method and guided by a conceptual framework that integrates the Social Ecological Model (SEM), the Health Belief Model and the Institute of Medicine's Healthcare Quality Framework. Results Barriers and facilitators were identified at several levels of the SEM. Among the main barriers reported by the study participants were: beliefs about illness, cancer stigma, cultural gender norms, access barriers to medical care, and mistreatment and discrimination by health care personnel. Our participants perceived as facilitators: information provided by doctors, social support, perceived severity of the disease and perceived benefits of seeking care for breast symptoms. Conclusions Healthcare policies need to be responsive to the particular barriers faced by indigenous women in order to improve their participation in early detection and early help-seeking of care for breast symptoms. Measures to prevent and eradicate all forms of discrimination in healthcare are required to improve the quality of healthcare provided and the trust of the indigenous population in healthcare practitioners.